Address Generation Apparatus And Method For Quadratic Permutation Polynomial Interleaver De-Interleaver - Lee, Shuenn-Gi; Wang, Chung-Hsuan; Sheen, Wern-Ho (My University, 2011)
An address generation apparatus for a quadratic permutation polynomial (QPP) interleaver is provided. It comprises a basic recursive unit, and L recursive units represented by first recursive unit up to Lth recursive units. The apparatus inputs a plurality of configurable parameters according to a QPP function Π(i)=(f1i+f2i2) mod k, generates a plurality of interleaver addresses in serial via the basic recursive unit, and generates L groups of corresponding interleaver addresses via the first up to the Lth recursive units, wherein Π(i) is the i-th interleaver address generated by the apparatus, f1 and f2 are QPP coefficients, and k is information block length of an input sequence, 0≦i≦k−1.